The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Diversity and spatial variability of shallow benthic macrofaunal assemblages in a high-Arctic fjord (Young Sound, North-East Greenland) - Guillaume Bridier; Frédéric Olivier; Lucas Pinsivy; Jérôme Jourde; Laurent Chauvaud; Mikael K. Sejr; Thomas Burel; Michel Le Duff; Jacques Grall (Polar Biology, 2024)

Comparison of supervised classifications to discriminate seaweed-dominated habitats through hyperspectral imaging data - Wendy Diruit; Thomas Burel; Touria Bajjouk; Anthony Le Bris; Sophie Richier; Sara Terrin; Mathieu Helias; Valérie Stiger-Pouvreau; Erwan Ar Gall (Journal of Applied Phycology, 2024)

Maerl-associated macroalgae in the bay of Brest (Brittany, France) - Mathieu Helias; Thomas Burel (Marine Biodiversity, 2023)

Wave height vs. elevation effect on macroalgal dominated shores: an intercommunity study - Thomas Burel; Jacques Grall; Gauthier Schaal; Michel Le Duff; Erwan Ar Gall (Journal of Applied Phycology, 2020)

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Functional landscape heterogeneity and animal biodiversity in agricultural landscapes - Lenore Fahrig; Jacques Baudry; Lluís Brotons; Françoise G. Burel; Thomas O. Crist; Robert J. Fuller; Clelia Sirami; Gavin M. Siriwardena; Jean‐Louis Martin (Ecology Letters, 2011)
Ecology Letters (2011) 14: 101–112 Abstract Biodiversity in agricultural landscapes can be increased with conversion of some production lands into ‘more‐natural’– unmanaged or extensively managed – lands. However, it remains unknown to what extent biodiversity can be enhanced by altering landscape pattern without reducing agricultural production. We propose a framework for this problem, considering separately compositional heterogeneity (the number and proportions of different cover types) and configurational heterogeneity (the spatial arrangement of cover types). Cover type classification and mapping is based on species requirements, such as feeding and nesting, resulting in measures of ‘functional landscape heterogeneity’. We then identify three important questions: does biodiversity increase with (1) increasing heterogeneity of the more‐natural areas, (2) increasing compositional heterogeneity of production cover types and (3) increasing configurational heterogeneity of production cover types? We discuss approaches for addressing these questions. Such studies should have high priority because biodiversity protection globally depends increasingly on maintaining biodiversity in human‐dominated landscapes.